Rethinking Italian Autonomist Marxism: Spatial Composition, Urban Contestation, and the Material Geographies of Social Reproduction. Issue 3 (13th January 2022) - Gray, Neil
Abstract: Class composition was the most important concept to be developed within the rich milieu of Italian autonomist Marxism, acutely addressing subject‐object dichotomies and organisational problems of internal differentiation in and between classed, raced and gendered social formations. Yet "compositionist" analysis has received remarkably little attention within urban‐geographical literatures. This paper reviews and develops the class composition concept, offering the first fully developed theorisation of spatial composition and underscoring its relevance for a contemporary politics of space. It stresses the importance of immanent, reflexive non‐teleological periodisations of capitalist relations for anti‐capitalist struggle through the intertwined concepts of spatial composition and the tendency. Through this theoretical lens it narrates the innovative and under‐examined spatial praxis of often women‐led urban movements in 1970s Italy, arguing that these remarkable struggles provide vital lessons for thinking through the diverse modalities of organisation and class recomposition emerging in the material geographies of social reproduction today.